CROSS-CORRELATIONS IN THE BROWNIAN MOTION OF COLLOIDAL NANOPARTICLES - KELEMEN, Sz.; VARGA, L.; NÉDA, Z. (Studia Universitatis Babeș-Bolyai Physica, 2020)
The two-body cross-correlation for the diffusive motion of colloidal nano-spheres is experimentally investigated. Polystyrene nano-spheres were used in a very low concentration suspension in order to minimize the three- or more body collective effects. Beside the generally used longitudinal and transverse component correlations we investigate also the Pearson correlation in the magnitude of the displacements. In agreement with previous studies we find that the longitudinal and transverse component correlations decay as a function of the inter-particle distance following a power-law trend with an exponent around -2. The Pearson correlation in the magnitude of the displacements decay also as a power-law with an exponent around -1.